Ghosts' high noon - Vipont, Elfrida (H. Z. Walck, 1967)
Ten tales of strange experiences and events told during a series of evenings by a family and their guests at an old country house in England.
Includes bibliographical references.
Ten tales of strange experiences and events told during a series of evenings by a family and their guests at an old country house in England.